Wounding, Doubting, and Trusting in Suffering - Tam, Ekman P. C. (The Journal of pastoral care, 2001)
Constructs a working model of pastoral care on the foundation of the reality of suffering. Explicates how suffering wounds the person both psychologically and spiritually and how doubting God can be a constructive phase leading to the reclaiming of trust in God.